A "4-cell" modular passive DMFC (direct methanol fuel cell) stack for portable applications. (15th March 2015) - Wang, Luwen; He, Mingyan; Hu, Yue; Zhang, Yufeng; Liu, Xiaowei; Wang, Gaofeng
Abstract: A "4-cell" modular passive DMFC (direct methanol fuel cell) stack, which can be freely combined and applied to various electronic devices, is designed, fabricated and tested. Two PCB (printed circuit board) based accessories are designed and fabricated for electrically connecting and mechanically assembling the "4-cell" modules. The maximum power density of the "4-cell" module is 27 mW cm −2 at 5 M methanol concentration. The steady-state performances of the modular stacks with different numbers of modules are tested. The extra power loss of the multiple module stacks due to inter-module electrical connections is predicted by mathematical fitting method. The fitting results indicate that the efficiencies of the multiple module stacks are all above 90% up to 10 modules. The dynamic performances of the modular stacks are also investigated for portable applications. The results show that the modular stacks exhibit good responsiveness and reproducibility at high loading current (>100 mA). Finally, the modular stacks are successfully applied to drive the experimental fan and charge the mobile phone. Highlights: A "4-cell" modular passive DMFC (direct methanol fuel cell) stack is designed, fabricated and tested. This modular DMFC stack can assemble more single cells with high efficiency. The modular stack exhibit good responsiveness and reproducibility for portable application.